Polyconjugation for Organic Electronics - Medina Rivero, Samara; Casado-Cordón, Juan (Gordon conference, 2022)
Since the discovery of the semiconducting properties of π-conjugated organic oligomers and polymers, many efforts have been devoted to generating structural features that bring about new and outstanding properties for optoelectronics, spintronics and magnetic devices, non-linear optics, or singlet fission processes. In this sense, the play between the resonance and π-electron delocalization phenomena in π-conjugated organic materials is the origin of their semiconducting behavior. For this reason, establishing not only the electron delocalization mechanism and its extension, but also which factors disturb the π-electron density is of utmost importance to enhance the proper performance of the electronic devices and develop ad hoc synthesis for desired application.
Polyconjugation for Organic Electronics
Keywords: Oligómeros (Polímeros); Optoelectrónica; Conjugation; Organic devices; Moléculas orgánicas policonjugadas